Development of Wireless Sensor Network for Traffic Monitoring Systems - Sanket Suresh Naik Dessai (Institute of Advanced Engineering and Science, 2014)
Traffic congestion has been a major problem on roads around the world. In addition, there is increase in volume of traffic vehicle density at a steady rate. Thus traffic on major roads has to be controlled to keep the traffic flowing at an acceptable rate. Several schemes for replacing the predominantly used Round Robin (RR) scheme for reducing congestion at traffic junctions have been proposed. Dynamic traffic control schemes adapt to the changing traffic by monitoring the state (such as the number queued up on each lane.). These need appropriate sensing and monitoring systems. In this paper a traffic monitoring and control system based on AMR (Anistropic Magneto Resistive) vehicle sensors, wireless sensor network and a proiritised Weighted Round Robin (WRR) scheduling technique, is developed.AMR sensors installed in road pavement detect the number of vehicles waiting in a traffic lane. The AMR sensors are connected to the master controller to form a Zigbee based sensor network. The master node consists of an ARM processor integrated with a Zigbee masternode. The traffic control algorithm is implemented at master node which is responsible for taking traffic signaling decision. It receives sensor data from all the lanes. A two level priority algorithm with weighted round robin scheduling, where first and second maximum weighted lane are to pass the signal is developed, To avoid starving the least loaded lanes, a cycle of normal round robin scheduling is performed after four rounds of proiritised weighted round robin schedule. The proposed algorithm is simulated and compared with the standard round robin algorithm. The developed algorithm decreases the average waiting time for a commuter while maintaining the average throughput up to average loads. The development traffic monitoring system is successfully demonstrated for a four lane junction.